HOP2–MND1 chaperones a diffusing DMC1–ssDNA complex to survey dsDNA for homology recognition during meiotic recombination - Bingkai Cheng; Yanan Li; Yi Zhao; Yuting Zhang; Xia Zhang; Lishuang Chen; Hao Yang; Xiaoxuan Song; Zhiyun Ren; Cong Liu; Jingdong Xue; Bing Li; et al. (Proceedings of the National Academy of Sciences, 2026)
Meiotic recombination ensures genetic diversity and accurate chromosome segregation by mediating reciprocal DNA exchange between homologous chromosomes. In this process, the meiosis-specific recombinase DMC1 plays a pivotal role in homology search and pairing, but the molecular mechanisms underlying its function remain unclear. Using single-molecule imaging, we demonstrate that the human DMC1–ssDNA presynaptic complex employs a diffusion-based mechanism to search for homologous DNA. Although this diffusing complex generates a migrating DNA “bubble,” it cannot align with the homologous sequence in the absence of free DMC1 protein. Strikingly, the meiosis-specific cofactor complex HOP2–MND1 compensates for the lack of free DMC1 and enables homology recognition. Notably, HOP2–MND1 achieves this by codiffusing with the presynaptic complex, acting to clamp the ssDNA–dsDNA junctions and maintain an expanded DNA bubble conducive to sequence alignment. Our findings identify DMC1 together with HOP2–MND1 as a functional homology search unit and provide mechanistic insights into how auxiliary factors regulate DMC1-driven strand exchange during meiotic recombination.